2020
DOI: 10.1002/14651858.cd009261.pub5
|View full text |Cite
|
Sign up to set email alerts
|

Negative pressure wound therapy for surgical wounds healing by primary closure

Abstract: BackgroundIndications for the use of negative pressure wound therapy (NPWT) are broad and include prophylaxis for surgical site infections (SSIs). While existing evidence for the effectiveness of NPWT remains uncertain, new trials necessitated an updated review of the evidence for the effects of NPWT on postoperative wounds healing by primary closure. ObjectivesTo assess the effects of negative pressure wound therapy for preventing surgical site infection in wounds healing through primary closure. Search metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
116
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(125 citation statements)
references
References 179 publications
3
116
0
6
Order By: Relevance
“…This may further explain our overall positive graft take rates in the first week. The removal of excess exudate through NPWT reduces the risk of hematoma formation and prevents the complications of graft shear or lift‐off 37‐39 ; this is consistent with our graft take results.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This may further explain our overall positive graft take rates in the first week. The removal of excess exudate through NPWT reduces the risk of hematoma formation and prevents the complications of graft shear or lift‐off 37‐39 ; this is consistent with our graft take results.…”
Section: Discussionsupporting
confidence: 89%
“…Our infection rate outcomes indicated a significant risk reduction, which is consistent with findings from several past reviews 17,39,43‐47 . It is suggested that NPWT decreases the infection rate due to the following reasons: For wound care management, the NPWT systems lower dressing frequency, the wound site would be exposed less 17,48,49 .…”
Section: Discussionsupporting
confidence: 89%
“…If they did not have any sign of sternum stabilization, they also were treated in the same way. Those with mediastinitis were applied with vacuum-assisted closure (VAC) in addition to anti biotherapy, according to the wound microgram culture result [Norman 2020]. Necrotic tissue was debrided, and the sternum was rewired after the infection was healed, and the sternum was covered with major pectus muscle [Elassal 2020].…”
Section: Methodsmentioning
confidence: 99%
“…However, the scope of this guideline is limited by the inherent bias of basing this decision on mainly nonrandomized studies [11–13]. A Cochrane meta‐analysis published in 2020 included 44 RCTs of different types of surgery and found ‘moderate‐certainty evidence' that SUNPDs reduce the incidence of SSI [14]. However, a meta‐analysis limited to laparotomies (elective and emergency) found no significant difference in the rate of SSI between negative‐pressure wound therapy and standard dressings [15].…”
Section: Introductionmentioning
confidence: 99%